2016
DOI: 10.1080/10298436.2016.1172706
|View full text |Cite
|
Sign up to set email alerts
|

New approaches for modelling subgrade nonlinearity in thin surfaced flexible pavements

Abstract: a griffith School of engineering, griffith university, gold Coast, australia; b Department of transport and main roads (Queensland), Brisbane, australia ABSTRACT The primary objective of this paper is to present new methods in characterising flexible pavements that possess nonlinear subgrade behavior using deflection data from falling weight deflectometer (FWD). The two techniques to be introduced are Simplified Deflection Modeling and Deflection Ratio (DefR) approach. FWD deflection data can be modelled accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For pavement design in Australia, D0 is the maximum deflection, D250 / D0 is the deflection ratio, D0 -D200 is the curvature function and the D900 reflects the subgrade response. Note, for subgrade response on thin pavements, recent research by Chai et al [8] should be considered. For calculating the pavement structural the FWD test data can be used.…”
Section: Option 1-annual Work Program Datamentioning
confidence: 99%
“…For pavement design in Australia, D0 is the maximum deflection, D250 / D0 is the deflection ratio, D0 -D200 is the curvature function and the D900 reflects the subgrade response. Note, for subgrade response on thin pavements, recent research by Chai et al [8] should be considered. For calculating the pavement structural the FWD test data can be used.…”
Section: Option 1-annual Work Program Datamentioning
confidence: 99%
“…The reason to choose the 900 D deflection is that QDMR (1990) has found that it reflects a subgrade response which remains essentially unaffected by the structure of the overlying pavement. Chai et al (2016) pointed out in the study that assessing the moisture content on the road is one of the applications of simplified deflection model. In addition, he plotted the relationship lines between the moisture content and the k2,900 according to SDM, as shown in Figure 9.…”
mentioning
confidence: 99%